(untitled) (Economic and Political Thought, 2015)
The aim of the article is to identify the stages of development of the American dollar and three currencies orbiting it (the euro, pound sterling and Swiss frank) with the use of econometric methods and to make comparisons in order to highlight the mechanisms of long-term changes in the value of world money. The author analysed not only the dynamics of currency exchange rates in time but also reason-effect relationship of the changes. This was used to develop the dollar’s value forecast until 2024 and the euro’s value one until 2020.